Artemisinin and Its Derivate Alleviate Pulmonary Hypertension and Vasoconstriction in Rodent Models. (17th June 2022) - Bao, Changlei; He, Qian; Wang, Hui; Sun, Yanan; Xu, Yahang; Pan, Yan; Hu, Yadan; Zheng, Shichuang; Liang, Shuxin; Luo, Ang; Nahar, Tanzilan; Chen, Jiwang; et al.
Abstract : Background . Pulmonary arterial hypertension (PAH) is a complex pulmonary vasculature disease characterized by progressive obliteration of small pulmonary arteries and persistent increase in pulmonary vascular resistance, resulting in right heart failure and death if left untreated. Artemisinin (ARS) and its derivatives, which are common antimalarial drugs, have been found to possess a broad range of biological effects. Here, we sought to determine the therapeutic benefit and mechanism of ARS and its derivatives treatment in experimental pulmonary hypertension (PH) models. Methods . Isolated perfused/ventilated lung and isometric tension measurements in arteries were performed to test pulmonary vasoconstriction and relaxation. Monocrotaline (MCT) and hypoxia+Su5416 (SuHx) were administered to rats to induce severe PH. Evaluation methods of ARS treatment and its derivatives in animal models include echocardiography, hemodynamics measurement, and histological staining. In vitro, the effect of these drugs on proliferation, viability, and hypoxia-inducible factor 1 α (HIF1 α ) was examined in human pulmonary arterial smooth muscle cells (hPASMCs). Results . ARS treatment attenuated pulmonary vasoconstriction induced by high K + solution or alveolar hypoxia, decreased pulmonary artery (PA) basal vascular tension, improved acetylcholine- (ACh-) induced endothelial-dependent relaxation, increased endothelial nitric oxide (NO) synthase (eNOS) activity and NO levels, and decreased levels of NAD(P)H oxidase subunits (NOX2 and NOX4) expression, NAD(P)H oxidase activity, and reactive oxygen species (ROS) levels of pulmonary arteries (PAs) in MCT-PH rats. NOS inhibitor, L-NAME, abrogated the effects of ARS on PA constriction and relaxation. Furthermore, chronic application of both ARS and its derivative dihydroartemisinin (DHA) attenuated right ventricular systolic pressure (RVSP), Fulton index (right ventricular hypertrophy), and vascular remodeling of PAs in the two rat PH models. In addition, DHA inhibited proliferation and migration of hypoxia-induced PASMCs. Conclusions . In conclusion, these results indicate that treatment with ARS or DHA can inhibit PA vasoconstriction, PASMC proliferation and migration, and vascular remodeling, as well as improve PA endothelium-dependent relaxation, and eventually attenuate the development and progression of PH. These effects might be achieved by decreasing NAD(P)H oxidase generated ROS production and increasing eNOS activation to release NO in PAs. ARS and its derivatives might have the potential to be novel drugs for the treatment of PH.